2018
DOI: 10.3390/cancers10040107
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Spectrum of Systemic Anaplastic Large Cell Lymphoma (ALCL)

Abstract: Anaplastic large cell lymphoma (ALCL) represents a group of malignant T-cell lymphoproliferations that share morphological and immunophenotypical features, namely strong CD30 expression and variable loss of T-cell markers, but differ in clinical presentation and prognosis. The recognition of anaplastic lymphoma kinase (ALK) fusion proteins as a result of chromosomal translocations or inversions was the starting point for the distinction of different subgroups of ALCL. According to their distinct clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 146 publications
(185 reference statements)
1
63
1
2
Order By: Relevance
“…In nearly half of the patients (46.0%), simultaneous involvement of both lymph nodes and extranodal organs was found on PET/CT in the present study. Among the extranodal organs, bone was demonstrated to be the most commonly involved organ, which is inconsistent with previously published articles have shown that the skin is the most common extranodal involvement site [4,20]. In our results, the skin was Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…In nearly half of the patients (46.0%), simultaneous involvement of both lymph nodes and extranodal organs was found on PET/CT in the present study. Among the extranodal organs, bone was demonstrated to be the most commonly involved organ, which is inconsistent with previously published articles have shown that the skin is the most common extranodal involvement site [4,20]. In our results, the skin was Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…To correlate the expression of the JAK-STAT signaling pathway with immunohistochemical and serological factors of disease pathology, we investigated EBV seropositivity, and expression of immunophenotype markers as defined with IHC ( Figure 6). Lower pY-STAT3 expression was associated with negative CD3 (37.7% and 75.4% mean pSTAT3 expression, p < 0.001, t-test), CD5 (42.8% and 68.4%, p = 0.03, t-test), CD7 (45.2% and 64.6%, p = 0.01) and positive CD30 phenotype ( Figure S4A) designating ALCL immunophenotype as reported in Figure 2 [30]. No association with EBV seropositivity ( Figure S4B), CD4 (p = 0.86, t-test) or CD8 (p = 0.35, t-test) immunophenotype nor MIB proliferation index (r = 0.20, p = 0.19, Pearson correlation) was noted.…”
Section: Stat3 Phosphorylation Is Associated With Jak1/stat3 Mutationmentioning
confidence: 72%
“…Malignant transformation by ALK involves several mechanisms including hyper-activation of Ras/MAPK-, PI3K-and STAT3 signaling pathways as well as increased expression of transcriptional regulators and stem-cell factors, which shifts the affected cell to a more undifferentiated state [69][70][71][72] . In this study, we conducted a genomewide deficiency screen in Drosophila to identify modifiers of Alk signaling, resulting in the identification of many known and anticipated signaling molecules, such as Ras/Raf/ERK network components (MESR3, Cnk, Aveugle), PI3K21B, STAT92E, and the protein serine/threonine phosphatase Alphabet which is in agreement with previous screening efforts 73 .…”
Section: Discussionmentioning
confidence: 99%